HUKUM ISLAM, KONSTITUSI, DAN MEDIA DIGITAL: Sebuah Studi Konstruksi Wacana Islam di Indonesia Kontemporer - Muji Buddin SM, M; Sulistio, Dody; Irfan Achfandhy, Mochammad; Alfan Sidik, Muhammad; Mubin, Muhammad Nurul (Al-Risalah, 2025)
Over the past decade, popular Islamic websites in Indonesia have functioned not only as platforms for da'wah but also as arenas for articulating and contesting legal and ideological discourses concerning Islam and the Constitution. This qualitative descriptive study employs Critical Discourse Analysis (CDA) to examine digital texts from four high-traffic Islamic websites: NU Online, Islami.co, Eramuslim.com, and Voa-Islam.com, identified using Alexa (2017–2019) and SimilarWeb (2020) data. The analysis reveals two dominant discursive formations. Legal-formalist platforms such as Eramuslim.com and Voa Islam.com, influenced by the DDII network, advocate for the constitutional integration of sharia, echoing the thought of Abu A‘la al-Maududi. In contrast, substantive contextual platforms such as NU Online and Islami.co emphasize ethical compatibility between Islamic values, democracy, and Pancasila, reflecting Abdullah Saeed’s humanistic interpretation of Islamic law. The findings demonstrate that digital media are not neutral conduits but sites of ideological negotiation where Islamic authority is reconfigured through communicative performance and platform logics that reward dialogical, verifiable, and inclusive narratives. The study contributes theoretically by extending Fairclough’s CDA into the digital ecology, linking textual analysis with metrics of visibility and communicative legitimacy.